2019
DOI: 10.3389/fgene.2018.00739
|View full text |Cite
|
Sign up to set email alerts
|

Defining Key Genes Regulating Morphogenesis of Apocrine Sweat Gland in Sheepskin

Abstract: The apocrine sweat gland is a unique skin appendage in humans compared to mouse and chicken models. The absence of apocrine sweat glands in chicken and murine skin largely restrains further understanding of the complexity of human skin biology and skin diseases, like hircismus. Sheep may serve as an additional system for skin appendage investigation owing to the distributions and histological similarities between the apocrine sweat glands of sheep trunk skin and human armpit skin. To understand the molecular m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 63 publications
2
7
0
Order By: Relevance
“…The inflammatory effects of LIF and IL-6 had been studied in mesenchymal cells 42 , and here we focused on IL-17B, an uncovered inflammatory ligand in mesenchymal cells and an IL-17 family member. We observed IL-17B co-expressed with PDGFRB+ mesenchymal cells in skin dermis layer, and the skin tissue distribution of PDGFRB protein was consistent with the previous studies 43 . Furthermore, we performed immunohischemistry staining for both healthy and psoriatic skin biopsies, and quantitatively compared the expression levels of PDGFRB and IL-17B protein.…”
Section: Resultssupporting
confidence: 92%
“…The inflammatory effects of LIF and IL-6 had been studied in mesenchymal cells 42 , and here we focused on IL-17B, an uncovered inflammatory ligand in mesenchymal cells and an IL-17 family member. We observed IL-17B co-expressed with PDGFRB+ mesenchymal cells in skin dermis layer, and the skin tissue distribution of PDGFRB protein was consistent with the previous studies 43 . Furthermore, we performed immunohischemistry staining for both healthy and psoriatic skin biopsies, and quantitatively compared the expression levels of PDGFRB and IL-17B protein.…”
Section: Resultssupporting
confidence: 92%
“…WIF1 belongs to the family of Wnt inhibitors, which interferes with Wnt signal transduction by directly binding to WNT proteins ( 41 ). The expression of WIF1 increased in the early stage of hair follicle growth ( 42 ), which was consistent with the results of this study. It is known that the expression of WNT11 is up-regulated during skin wound healing, indicating that the signal transduction of this gene may be active in the stage of wound healing and play an important role in the regeneration of hair follicles ( 43 ).…”
Section: Discussionsupporting
confidence: 92%
“…Previous transcriptome studies have reported the gene expression atlas for multiple domestic animals, including cattle, pigs, goats, sheep, and water buffalo [ 18 , 24 27 ]. Differentially expressed genes (DEGs) or core driver genes were identified as potential candidates, which were involved in important functions, including growth and development [ 28 , 29 ], meat quality [ 30 , 31 ], wool follicle [ 32 , 33 ], and disease-resistance [ 34 , 35 ]. Meanwhile, organ and tissue-specific gene expression patterns were also studied in farm animals [ 18 , 36 38 ], and these analyses further facilitated the elucidation of the relationship between gene expression, tissue, and organ.…”
Section: Introductionmentioning
confidence: 99%